Ambient air pollution and the risk of pediatric-onset inflammatory bowel disease: A population-based cohort study. (May 2020) - Elten, Michael; Benchimol, Eric I.; Fell, Deshayne B.; Kuenzig, M. Ellen; Smith, Glenys; Chen, Hong; Kaplan, Gilaad G.; Lavigne, Eric
Highlights: High-income nations have the highest rates of inflammatory bowel disease. Exposure to Ox during childhood was associated with IBD < 18 years. Ambient air pollution is suspected to be associated with risk of IBD. Abstract: Background: High-income nations have the highest rates of inflammatory bowel disease (IBD). The incidence of pediatric-onset IBD is increasing faster than IBD diagnosed in older individuals. Previous epidemiological studies have shown that air pollution might be a risk factor for development of earlier-onset IBD, but results remain mixed. Objectives: The objective of this study was to evaluate the associations between maternal and early-life exposures to nitrogen dioxide (NO2 ), fine particulate matter (PM2.5 ), ozone (O3, ) and oxidant capacity (Ox ) and risk of pediatric-onset IBD diagnosis. Methods: We conducted a retrospective cohort study using linked population-based health administrative data. Singleton livebirths in Ontario, Canada between April 1st, 1991 and March 31st, 2014 were included. We investigated the association between weekly exposures during pregnancy and annual exposures from birth until the age of 18 years, and IBD diagnosed <18 years of age using Cox proportional hazards models. We reported hazard ratios (HR) and 95% confidence intervals (CI) for an associated increase in the interquartile range (IQR) of each pollutant. Models were mutually adjusted for exposures in both prenatal and postnatal periods, as well as for sex, rurality of residence at birth, maternal IBD, and neighborhood income. Results: 2, 218, 789 newborns were included in this study, of whom 2491 developed IBD during follow-up. Increased associations with pediatric-onset IBD were noted for childhood exposure to Ox (HR 1.08, 95% CI 1.01–1.16). IBD development was also associated with Ox during the second trimester (HR 1.21, 95% CI 1.03–1.42), but not the overall pregnancy period (HR 1.12, 95% CI 0.79–1.59). There were no associations of IBD with exposure to NO2, PM2.5, or O3 . Discussion: Exposure to Ox during childhood was associated with IBD < 18 years. This suggests that air pollution may impact the developing child physiology in such a way that leads to early onset of IBD.